Modeling of plastics coextrusion. Part I. Viscous flows - Wilczyński, K.; Szymaniak, Z.; Nastaj, A. (Polimery, 2022)
A method of modeling of free multilayer forming problem occuring in the coextrusion process was presented. The modelling concerned chosen bilayer annular Newtonian flows (Fig. 4), at isothermal conditions, for various flow rate and viscosity values (Figs. 5-18). It has been stated that differences in viscosity of flow material result in displacement of polymer stream towards the more viscous phase and displacement of the maximum at velocity profile to the opposite direction. Instead the differences in flow rate result in transferring of the interface towards the phase of smaller flow rate. The known phenomenon of the stream swelling during Newtonian flow has been confirmed.